Alien toxic dinoflagellate Heterocapsa circularisquama from the Western Pacific in Kuwait, NW Indian Ocean. (February 2022) - Saburova, Maria; Al-Kandari, Manal; Polikarpov, Igor; Akbar, Abrar; Hussain, Sumaiah; Rahmeh, Rita; Al-Zakri, Waleed; Al-Yamani, Faiza
Abstract: A bloom of non-indigenous dinoflagellate Heterocapsa circularisquama (Peridiniales, Dinophyceae) and bloom-associated shellfish mortality were detected for the first time in Kuwait's waters (Arabian/Persian Gulf, NW Indian Ocean) during June–July 2020. This species is endemic to the Asia Pacific region, and associated with shellfish kills, causing tremendous damage to bivalve aquaculture, and economic losses in western Japanese waters and Hong Kong. In Kuwait Bay, this dinoflagellate was found in bloom proportions up to 10 8 cells·l −1 and represented from 72 to 83% of the total phytoplankton population in red tide patches. Native bloom-forming small-sized diatoms, Thalassiosira delicatula, T. exigua, and Minutocellus polymorphus were also abundant at the time of the H. circularisquama bloom. Microalgal cell morphology was determined using light and electron microscopy for specimens from the field and cultures established by cell isolation from the bloom area. The molecular characterization of cultured Heterocapsa strains was based on the large subunit region of the ribosomal DNA sequences. The overall morphology and body scale structure of Heterocapsa from Kuwait Bay were very similar to that of the H. circularisquama described from Japanese waters. The sequences of the LSU rDNA of Kuwait's strains were identical to those of the H. circularisquama . This is the first record of H. circularisquama occurring at high abundance outside the Asia Pacific region, and it may be an indication this invasive and harmful species is now established in Kuwait's marine environment. Highlights: Heterocapsa circularisquama is discovered for the first time in the NW Indian Ocean. Morphological and molecular data confirmed the species identity. Bloom of Heterocapsa circularisquama caused mortality in bivalves. Heterocapsa circularisquama represents an invasive and harmful species to Kuwait.